THE IMPACT OF THE GREEN MARCH ON MODERN MOROCCAN SOCIETY - Zamakda Allison, Safwaan (Universitas Nasional, 2021)
This research aims to examine (a) the historical context of the Moroccan Green March and (b) the impact of this profound social, political, economic, military, and religious event on modern day Moroccan society and culture. this research adopted a mixed-methods approach, with the qualitative approach being substantially dominant, so that the authentic and unfettered views of Moroccan citizens can be presented. In respect of statecraft, the Kingdom of Morocco has performed admirably. As per the US Department of State, â€œThe Kingdom of Morocco claims the territory of Western Sahara and administers the territory that it controlsâ€. This shows that the Green March has led to concrete steps, on the ground action, and the development of the region. It is further stated that â€œMoroccan law and practice apply [in Western Sahara]. The impetus for this action came from within society, not from the Monarch of government. The Green March has a substantial effect on Moroccan society to this day, and songs are sung about it (such as â€˜Sawt El Hassanâ€™) and postage stamps are issued to commemorate the momentous event.